Detection of Hepatitis B Virus–Host Junction Sequences in Urine of Infected Patients. Issue 10 (25th August 2021) - Lin, Selena Y.; Su, Yih‐Ping; Trauger, Evan R.; Song, Benjamin P.; Thompson, Emilie G.C.; Hoffman, Malcolm C.; Chang, Ting‐Tsung; Lin, Yih‐Jyh; Kao, Yu‐Lan; Cui, Yixiao; Hann, Hie‐Won; Park, Grace; et al.
Abstract : Integrated hepatitis B virus (HBV) DNA, found in more than 85% of HBV‐associated hepatocellular carcinomas (HBV‐HCCs), can play a significant role in HBV‐related liver disease progression. HBV‐host junction sequences (HBV‐JSs), created through integration events, have been used to determine HBV‐HCC clonality. Here, we investigate the feasibility of analyzing HBV integration in a noninvasive urine liquid biopsy. Using an HBV‐targeted next‐generation sequencing (NGS) assay, we first identified HBV‐JSs in eight HBV‐HCC tissues and designed short‐amplicon junction‐specific polymerase chain reaction assays to detect HBV‐JSs in matched urine. We detected and validated tissue‐derived junctions in five of eight matched urine samples. Next, we screened 32 urine samples collected from 25 patients infected with HBV (5 with hepatitis, 10 with cirrhosis, 4 with HCC, and 6 post‐HCC). Encouragingly, all 32 urine samples contained HBV‐JSs detectable by HBV‐targeted NGS. Of the 712 total HBV‐JSs detected in urine, 351 were in gene‐coding regions, 11 of which, including TERT (telomerase reverse transcriptase), had previously been reported as recurrent integration sites in HCC tissue and were found only in the urine patients with cirrhosis or HCC. The integration breakpoints of HBV DNA detected in urine were found predominantly (~70%) at a previously identified integration hotspot, HBV DR1‐2 (down‐regulator of transcription 1‐2). Conclusion: HBV viral–host junction DNA can be detected in urine of patients infected with HBV. This study demonstrates the potential for a noninvasive urine liquid biopsy of integrated HBV DNA to monitor patients infected with HBV for HBV‐associated liver diseases and the efficacy of antiviral therapy. Abstract : image